Adding value to the VRIO framework using DEMATEL - Lacaze, A.; Ferreira, F.; Santos, M. (Management Decision, 2025)
Purpose Strategic management plays a pivotal role in the growth and success of organizations, significantly impacting their business performance and competitive edge. In today’s globalized markets, strategic management is gaining prominence as a means to enhance company performance and distinctiveness. Within this landscape, the evaluation of organizational effectiveness takes on heightened significance, complemented by the emergence of strategic management frameworks designed to secure enduring competitive advantages for businesses. Design/methodology/approach One of the best known approaches to organizational resource assessment is the value, rarity, inimitability and organizational-oriented (VRIO) framework. However, this tool comes with inherent limitations that have hindered its advancement, primarily related to the need for less subjective means of identifying and assigning weights to resources and capabilities during the evaluation process. This study, therefore, endeavored to refine the VRIO framework, making it more transparent and empirically robust. To achieve this aim, the framework was combined with the decision-making trial and evaluation laboratory (DEMATEL) method (i.e. a multiple criteria decision analysis (MCDA) method), and a real-life application was conducted. Findings The evaluation system created was tested, and the results demonstrate that the dual methodology used can increase the understanding of resource appraisal and lead to more informed and potentially better evaluations of resources and capabilities. The strengths and shortcomings of this new structured evaluation model are also analyzed. Originality/value The authors know of no prior work reporting the integrated use of VRIO and DEMATEL in this study context.